2018
DOI: 10.1007/s10897-018-0265-1
|View full text |Cite
|
Sign up to set email alerts
|

Disability Experiences and Perspectives Regarding Reproductive Decisions, Parenting, and the Utility of Genetic Services: a Qualitative Study

Abstract: Genetic counselors adopt seemingly contradictory roles: advocating for individuals with genetic conditions while offering prenatal diagnosis and the option of selective termination to prevent the birth of a child with a disability. This duality contributes to the tension between the disability and clinical genetics communities. Varying opinions exist amongst the disability community: some value genetic services while others are opposed. However, there is limited research exploring the opinions of individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Previous research on attitudes toward screening and selective reproduction has been somewhat contradictory. Some studies have revealed widespread support for selective reproduction amongst affected families and adults (e.g., Chen & Schiffman, 2000;Conway, Allenby, & Pond, 1994;Janssens et al, 2016;Potrata, McKibbin, Lim, & Hewison, 2014), whilst more recent research points to ambivalence and conflict (Maxwell et al, 2011), and sometimes outright rejection of the notion of screening on principle (Barter, Hastings, Williams, & Huws, 2016;Boardman & Hale, 2018;Roadhouse et al, 2018). Concerns have been expressed about the loss of (potentially) high quality life in spite of genetic disease, the implied implicit judgement on the value of life with disability and disapproval of the redirection of resources away from social and environmental barrier removal and toward the medical elimination of the condition (Boardman & Hale, 2018;Middleton, Hewison, & Mueller, 1998;Roadhouse et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on attitudes toward screening and selective reproduction has been somewhat contradictory. Some studies have revealed widespread support for selective reproduction amongst affected families and adults (e.g., Chen & Schiffman, 2000;Conway, Allenby, & Pond, 1994;Janssens et al, 2016;Potrata, McKibbin, Lim, & Hewison, 2014), whilst more recent research points to ambivalence and conflict (Maxwell et al, 2011), and sometimes outright rejection of the notion of screening on principle (Barter, Hastings, Williams, & Huws, 2016;Boardman & Hale, 2018;Roadhouse et al, 2018). Concerns have been expressed about the loss of (potentially) high quality life in spite of genetic disease, the implied implicit judgement on the value of life with disability and disapproval of the redirection of resources away from social and environmental barrier removal and toward the medical elimination of the condition (Boardman & Hale, 2018;Middleton, Hewison, & Mueller, 1998;Roadhouse et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al, 2015;Barlevy, Wasserman, Stolerman, Erskine, & Dolan, 2012;Chen & Schiffman, 2000;Middleton, Hewison, & Mueller, 1998). These attitudes are influenced by personal attitudes about and experiences with disability, as well as disability identity and involvement with disability culture and community 1 (Boardman & Hale, 2018;Boardman, Young, & Griffiths, 2018;Gollust, Thompson, Gooding, & Biesecker, 2003;Roadhouse et al, 2018;Stern et al, 2002).…”
mentioning
confidence: 99%
“…While the majority of the surrounding literature on reproductive decisions and attitudes within affected families have tended to focus on carrier parents (Al-Jader, Goodchild, & Harper, 1990;Henneman, Kooij, Bouman, & Kate, 2002;Kelly, 2009;McClaren et al, 2010;Miller & Schwartz, 1992;Skinner, Sparkman, & Bailey, 2003;Watson, Williamson, & Chapple, 1991), a limited number of studies have emerged that consider the views of genetically disabled adults (both physically and cognitively impaired) toward prenatal diagnosis and selective reproduction. These studies have produced a complex picture, with some finding support (Chen & Schiffman, 2000;Conway, Allenby, & Pond, 1994;Janssens et al, 2016), reticence (Barter, Hastings, Williams, & Huws, 2016;Janssens et al, 2015;Kelly, 2009), and also ambivalence (Roadhouse et al, 2018;Stern et al, 2002;Taneja, Pandya, Foley, Nicely, & Arnos, 2004;Ward, Howarth, & Rodgers, 2002) toward genetic technologies. Despite these limited studies, there has nevertheless been a general lack of analytic interface between the way(s) in which people experience, and assign value to, their impairment, and how this relates to their views on genetic carrier screening for it.…”
mentioning
confidence: 99%